Stereoselective construction of steroidal side chain from 16-dehydropregnenolone acetate - Aher, Nilkanth G.; Gonnade, Rajesh G.; Pore, Vandana S. (Synlett, 2009)
Stereoselective construction of steroidal side chain at C-20 having `natural' configuration using 16-dehydropregnalone acetate (16-6PA) as a starting material has been carried out. Palladium-catalyzed carbon-carbon bond-forming Heck reaction between C-20 vinyl iodide with methyl acrylate and transfer hydrogenation with triethylsilane and Pd/C are the key steps for stereoselective side-chain synthesis.
Keywords: 16-dehydropregnenolone acetate; Heck coupling; stereoselectivity; steroidal side chain; transfer hydrogenation